Do Financial Incentives Affect Utilization for Chronically Ill Medicare Beneficiaries?. Issue 4 (25th April 2022) - Buttorff, Christine; Girosi, Federico; Lai, Julie; Taylor, Erin A.; Lewis, Sarah E.; Ma, Sai; Eibner, Christine
Abstract : Objective: The objective of this study was to examine the price sensitivity for provider visits among Medicare Advantage beneficiaries. Data Sources: We used Medicare Advantage encounter data from 2014 to 2017 accessed as part of an evaluation for the Center for Medicare & Medicaid Innovation. Study Design: We analyzed the effect of cost-sharing on the utilization of 2 outcome categories: number of visits (specialist and primary care) and the probability of any visit (specialist and primary care). Our main independent variable was the size of the copayment for the visit, which we regressed on the outcomes with several beneficiary-level and plan-level control variables. Data Collection/Extraction Methods: We included beneficiaries with at least 1 of 4 specific chronic conditions and matched comparison beneficiaries. We did not require beneficiaries to be continuously enrolled from 2014 to 2017, but we required a full year of data for each year they were observed. This resulted in 371, 140 beneficiary-year observations. Principal Findings: Copay reductions were associated with increases in utilization, although the changes were small, with elasticities <−0.2. We also found evidence of substitution effects between primary care provider (PCP) and specialist visits, particularly cardiology and endocrinology. When PCP copays declined, visits to these specialists also declined. Conclusions: We find that individuals with chronic conditions respond to changes in copays, although these responses are small. Reductions in PCP copays lead to reduced use of some specialists, suggesting that lowering PCP copays could be an effective way to reduce the use of specialist care, a desirable outcome if specialists are overused.